ANALISIS POTENSI PENERIMAAN RETRIBUSI PASAR SEBAGAI SALAH SATU SUMBER PENDAPATAN ASLI DAERAH KABUPATEN HULU SUNGAI UTARA - Ahsani Fauzan (Jurnal Ekonomi Pembangunan, 2015)
Market  retribution market is one of sources of local revenue in Hulu Sungai Utara. The purpose of this study is to measure the potential revenue, market in Hulu Sungai Utara, which results will be used as a basic reference potential measure the effectiveness of revenue, market, in order to assess the results of the performance of market fee collection. This type of research is research diskiptif, while the data analysis method in use is the qualitative method, ie with a portrait, explain, and interpret the date obtained and analyzed to obtain conclusions.Contribution revenue, market on revenue is relatively small with only contributes a percentage rate 5%, from the year 2009 until the year 2012 revenue, always increasing but retribution market acceptance of is not comparable to the total revenues of local revenue Hulu Sungai Utara. Development of retribution market has increased every year, but in 2012 the increase in 2011 the difference is slight. Revenue, market the Department of Revenue in Hulu Sungai Utara against the target revenue, the market has not reached that yet effective, this is due to the realization of revenue, the market does not meet the expected targets, while potential market acceptance levy of 11 kinds of receipts in Hulu Sungai Utara Rp 1.947.378.000. The number is the whole of the potential is there, but can be developed by adding new facilities.